2022
DOI: 10.1097/md.0000000000028329
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin-A reduced the cytotoxicity of propranolol in HUVECs via p38 MAPK signaling

Abstract: Propranolol (PROP) is a nonselective β-adrenergic receptor antagonist used to treat hypertension and cardiac arrhythmias. Oral administration of PROP has recently emerged as a new treatment modality for hemangiomas. However, the side effects of PROP at the cellular level have not been adequately described. The present study investigates and highlights the mechanisms of coupling of the drugs cyclosporin-A (CyA) and PROP on cell proliferation and the occurrence of apoptosis. It also relays the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In agreement, previous studies reported that propranolol significantly downregulates B cell lymphoma-2 and BCl-2 associated X protein, which may be related to the TLR4/NF-κB (p65) signal in isoproterenol-induced myocardial fibrosis in mice [ 179 , 180 , 181 ]. Recently, studies demonstrated that propranolol revealed significant suppression of p38 protein expression that primarily regulates cell proliferation, migration, cell differentiation, and BCL-2 family, inhibiting apoptosis [ 182 , 183 ]. In addition, BCl-2 is considered a tissue homeostasis indicator in vascular, heart, and neurodegenerative diseases [ 184 , 185 ].…”
Section: Resultsmentioning
confidence: 99%
“…In agreement, previous studies reported that propranolol significantly downregulates B cell lymphoma-2 and BCl-2 associated X protein, which may be related to the TLR4/NF-κB (p65) signal in isoproterenol-induced myocardial fibrosis in mice [ 179 , 180 , 181 ]. Recently, studies demonstrated that propranolol revealed significant suppression of p38 protein expression that primarily regulates cell proliferation, migration, cell differentiation, and BCL-2 family, inhibiting apoptosis [ 182 , 183 ]. In addition, BCl-2 is considered a tissue homeostasis indicator in vascular, heart, and neurodegenerative diseases [ 184 , 185 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, cyclosporin A induces apoptosis, leading to mitochondrial damage and EMT at concentrations between 1 and 5 µM [ 30 , 31 , 32 ]. On the other hand, it protects against apoptosis and EMT induced by other substances at similar concentrations [ 33 , 34 ]. Future studies will reveal which of the acute effects is causing the observed cytotoxicity in our model.…”
Section: Discussionmentioning
confidence: 99%